2012
DOI: 10.1007/s00204-012-0942-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chronic fluorosis on mitochondrial dynamics morphology and distribution in cortical neurons of the rat brain

Abstract: The present study was designed to evaluate the effects of chronic fluorosis on the dynamics (including fusion and fission proteins), fragmentation, and distribution of mitochondria in the cortical neurons of the rat brain in an attempt to elucidate molecular mechanisms underlying the brain damage associated with excess accumulation of fluoride. Sixty Sprague-Dawley rats were divided randomly into three groups of 20 each, that is, the untreated control group (drinking water naturally containing <0.5 mg fluoride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…On the other hand, fluoride exposure led to upregulated vesicle-associated membrane protein-2 (VAMP-2) ( Han et al 2014 ) in hippocampus and dysregulated intercellular Ca 2+ in vitro ( Xu Z et al 2013 ; Zhang J et al 2011 ). Other potential mechanisms include increased ERK1/2 ( Liu et al 2010 ), JNK ( Liu YJ et al 2011 ), and NF-κB ( Zhang J et al 2011 ) expression, microglia activation ( Yan et al 2013 ), abnormal mitochondrial dynamics ( Lou et al 2013 ), hippocampus glutamate alterations ( Niu et al 2009 ), and altered acetylcholine receptors and cholinesterase ( Liu et al 2010 ; Zhao and Wu 1998 ). Ginkgo biloba extract ( Zhang et al 2013 ) and selenium ( Qian et al 2013 ) had neuroprotective effects.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, fluoride exposure led to upregulated vesicle-associated membrane protein-2 (VAMP-2) ( Han et al 2014 ) in hippocampus and dysregulated intercellular Ca 2+ in vitro ( Xu Z et al 2013 ; Zhang J et al 2011 ). Other potential mechanisms include increased ERK1/2 ( Liu et al 2010 ), JNK ( Liu YJ et al 2011 ), and NF-κB ( Zhang J et al 2011 ) expression, microglia activation ( Yan et al 2013 ), abnormal mitochondrial dynamics ( Lou et al 2013 ), hippocampus glutamate alterations ( Niu et al 2009 ), and altered acetylcholine receptors and cholinesterase ( Liu et al 2010 ; Zhao and Wu 1998 ). Ginkgo biloba extract ( Zhang et al 2013 ) and selenium ( Qian et al 2013 ) had neuroprotective effects.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate fluoride exposure and usage is beneficial to tooth integrity and, as such, has an important, positive impact on health throughout life [65], while water fluoridation also brings about negative impact such as the chronic toxicity of fluoride [66]. Chronic fluorosis has been found to cause damage to the central nervous system and cognitive impairment [20,21,[24][25][26][27]67], but the relationship between fluoride and AD is still elusive. In present study here, we found that long-term exposure to fluoride (especially exposure to low fluoride) could enhanced the deficit in Table 3 The MDA content and activities of SOD and GSH-Px in the brains of mice following 12 weeks of exposure to fluoride learning and memory and raised the numbers of senile plaque in mice carrying APP/PS1 double-transgenic mutation, which suggesting that long-term exposure to fluoride may be considered as risk factor of in development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride injures the central nervous system (CNS) by several mechanisms [18][19][20], in particular by elevating the level of oxidative stress [21][22][23][24]. Earlier studies in our own laboratory have documented direct toxic effects on the brains of experimental animals exposed to high levels of fluoride, including enhanced oxidative stress, reduction in the levels of nicotinic and muscarinic acetylcholine receptors, and mitochondrial abnormalities, along with impaired learning and memory [21,[24][25][26][27]. Moreover, fluoride increases lipid peroxidation and decreases the activity of antioxidant enzymes in rats, causing neurotoxicity, even in the second and third generations following exposure [28].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride accumulation in brain was observed in chronic high-fluoride exposure through drinking water. It is reported that high fluoride is known to cause structural and functional changes in the brain of experimental animals [3]. Evidence from clinical and animal model studies demonstrates that fluoride content may increases with age.…”
Section: Introductionmentioning
confidence: 99%